Water Quality on the Lower River Jeneberang: The impact of social distancing during the Covid 19 pandemic - Munawir Amansyah; Alwiyah Nur Syarif (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2021)
Diseases caused by the corona virus 2019-2020 (COVID-19) are public health problems that hit various countries, including Indonesia. Physical distancing is one of the suggested options to reduce the spread of the virus, but it can cause a lot of waste products generated by the community. This study aims to determine the quality of the waters using the water pollution index method on the coast of Makassar City as the mouth of the Jeneberang river as the impact of waste disposal during physical restrictions. This research is a quantitative study with a descriptive-observational design located in the downstream area of the Jeneberang River and the coastal area of Makassar City, Tamalate District, Makassar City. There are 8 points of measurement and sampling of river and seawater with different characteristics at each station. The measurement results of physical, biological, and chemical parameters, show that the average station is in the heavily polluted category, which means that the Jeneberang River during the pandemic has experienced a significant decrease in water quality. This study implies that the presence of people at home during social restrictions needs to be balanced with efforts to maintain a good waste management environment so as not to pollute the waters